ANALISIS KINERJA UMKM SKALA LOKAL - irfangi, ahmad; Luqmanudin, Teguh (STMIK Komputama Majenang, 2021)
Currently, MSMEs continue to make improvements so that their productivity continues to increase. From year to year there are no Micro Enterprises that are able to advance to class. The low performance and productivity of MSMEs, especially Micro Enterprises, is certainly caused by several things. This will be described in this paper. carried out on MSMEs assisted by the Nurjalin Cilacap Foundation, totaling 16 MSMEs and spread in 4 provinces throughout Indonesia. The method used for sampling is the purposive random sampling method, where the sampling is random, but there are certain limiting criteria related to the suitability of the research objectives and is only limited to MSMEs assisted by the Nurjalin Cilacap Foundation. The number of samples taken entirely from the existing population or known as saturated sampling technique. The conclusion of this study is that the Individual Characteristic variable has a positive and significant effect on Performance and the External Factor variable has a negative and significant effect on Performance.